The Downfall of KP Oli Government: Critical Analysis of Youth Uprising, Deep State, and Opposition Politics - Timalsina, Saroj Kumar; Shrestha, Suman Kumar (Educational Journal, 2026)
Several explanations ranging from constitutional crisis, party politics, poor foreign policies, and institutional conflicts have been advanced regarding the downfall of KP Sharma Oli's government in Nepal. But a close analysis would suggest that the Gen-Z protest had both symbolic and operational significance leading to the downfall of his government. This essay will argue that, although there is a truth in the adolescent frustration and anger expressed by teenagers in their protests, there were several elements of political conspiracy, consolidation, and geopolitics in the resultant political crisis. Through a theoretical lens incorporating theories on youth movement, deep-state research, and South Asian Political Economy, this essay seeks to examine the interconnection between modern-age networked social mobilization through the internet and the old structures of power hierarchy. A qualitative review of the relevant secondary literature highlights the significant roles played by internet disinformation campaigns and international politics in making the Gen Z protests morally right for elites who had designs on regime change. The essay contributes to the body of knowledge by filling an existing gap in the literature regarding the influence of youth activism on regime change. Recommendations are for inclusive youth involvement, institutional reforms, and transparency of governance to make Nepal's democracy less vulnerable to elite manipulation by using popular uprisings as cover. The paper develops a conceptual framework that connects structural, institutional, and generational processes while discussing some of the most recent research on youth agency during regime change. According to the report, rival players both inside and outside of Nepal dragged the Oli government down in addition to the unplanned youth protests. To reduce the likelihood of elite manipulation in the form of mass upheavals, policy recommendations urge youth involvement through participatory avenues, institutional change, and state transparency.